Physical, mechanical and thermal properties of pineapple leaf fibers and PALF-reinforced vinyl ester composites - Abd. Rahman, Mohamed (2010)
Despite being mechanically and environmentally sound, pineapple leaf fibers (PALF) are the least studied natural fibers especially as reinforcement in polymer composites and currently of little use in Malaysia. As the industrial importance and plantation area increase, efforts to develop applications utilizing PALF and simultaneously reduce environmental pollution must be carried out. This thesis aimed to contribute by studying a few fundamental aspects of PALF and PALF-reinforced composites. As species strongly dictates natural fiber properties, PALF from the three most popular Malaysian cultivars were characterized physically, mechanically and thermally. Effects of a simple abrasive combing and pretreatments on PALF properties were evaluated. PALF were used to reinforce vinyl ester resin (VER) using liquid composite molding (LCM) and the composite properties compared with those of hand-laid neat VER, glass fiber and PALF-VER composites. A factorial study was carried out on the effects and interactions of catalyst amount and selected process parameters on the properties of LCM VER sheets. Influence of fiber diameter, fiber property-retention after long storage, simple pretreatments, fiber location on the leaves and fiber separation techniques on mechanical properties of PALF-VER composites were also investigated. PALF tensile strength fits well with two-parameter Weibull distribution. Though uncritical for PALF-thermoset composites, the 20oC difference in thermal stability of PALF of different varieties is significant for PALF-thermoplastic composites. Josapine cultivar is the most appropriate PALF species in terms of potential fiber quantity, fineness, high tensile strength and modulus, thermal stability and ease of extraction. Vascular bundles and fiber strands were similar chemically and structurally thus differed by diameter only. The former were effectively stronger due to the presence of bonding tissues. Bundles from different locations in the leaves and those stored for a six-month period in hot humid conditions may be used without significantly affecting composite mechanical properties. At low weight fraction and consolidating pressure, PALF regardless of diameters and locations performed equally well in enhancing flexural properties in static loading. Composite toughness was higher when fine strands were used. Washing PALF with water improved PALF-VER adhesion while prolonged soaking produced no extra benefits. PALF and PALF-VER adhesion were not improved with the use of dilute aqueous sodium hypochlorite solution. Abrasive combing viably separated and produced fine and clean PALF of reasonable properties. Abrasive-combed PALF equaled technical fibers in reinforcing VER while their lower ductility reduced composite toughness. Untreated PALF bundles may be used to reinforce VER to produce real composites using LCM with water resistance significantly enhanced by molding pressure. Judicious process parameter selection is required to produce quality VER sheets and by extension PALF-VER composites. Molding VER-unsaturated polyester blend resulted in a significantly different material and a potential matrix for PALF composites.